Practical Fischer Indolization Using Bench-Stable Arylhydrazine Sulfonate as the Surrogate of Arylhydrazine - Li, Wenjuan; Shen, Chaoren; Zhu, Yanping; Dong, Kaiwu (Synlett, 2023)
Fischer indolization using bench-stable sodium arylhydrazine sulfonate as a surrogate of arylhydrazine was developed. The preparation of arylhydrazine sulfonate was also modified by replacing sodium sulfite reductant with Pd-catalyzed hydrogen transfer. The straightforward synthesis of tetrahydrocarbazoles from the corresponding anilines was successfully conducted in a one-pot manner. A practical application of this method was demonstrated in the formal synthesis of pharmaceutical molecules Rizatriptan and Zolmitriptan.
Keywords: arylhydrazine sulfonate; desulfonation; Fischer indolization; tryptamine; Rizatriptan; Zolmitriptan